2021
DOI: 10.1101/2021.03.25.437074
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unlimited cooperativity ofBetatectivirusSSB, a novel DNA binding protein related to an atypical group of SSBs from protein-primed replicating bacterial viruses

Abstract: Bam35 and related betatectiviruses are tail-less bacteriophages that prey on members of the Bacillus cereus group. These temperate viruses replicate their linear genome by a protein-primed mechanism. In this work, we have identified and characterized the product of the viral ORF2 as a single-stranded DNA binding protein (hereafter B35SSB). B35SSB binds ssDNA with great preference over dsDNA or RNA in a sequence-independent, highly cooperative manner that results in a non-specific stimulation of DNA replication… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 95 publications
(168 reference statements)
0
3
0
Order By: Relevance
“…Recently it was shown that Bam35 SSB binds ssDNA in a highly cooperative, yet sequence-independent manner. Additionally, Bam35 SSB and the phage phi29-related SSB proteins, seem to be forming a novel clade of SSBs from protein-primed replicating viruses that share a highly divergent OB-fold-like domain [ 46 ]. Maximum likelihood phylogeny reconstruction among SSB proteins with OB-fold ( Figure S2b ) indicated two well separated clusters: one grouping betatectiviruses Sato and Sole with more classical OB-fold SSBs, including the previously mentioned SSBs from S. aureus, B. subtilis and H. pylori and, the second cluster containing other betatectiviruses (i.e., Bam35, GIL01, GIL16 and AP50) along with protein-primed replicating phages belonging to the subfamily Picovirinae (family Salasmaviridae ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently it was shown that Bam35 SSB binds ssDNA in a highly cooperative, yet sequence-independent manner. Additionally, Bam35 SSB and the phage phi29-related SSB proteins, seem to be forming a novel clade of SSBs from protein-primed replicating viruses that share a highly divergent OB-fold-like domain [ 46 ]. Maximum likelihood phylogeny reconstruction among SSB proteins with OB-fold ( Figure S2b ) indicated two well separated clusters: one grouping betatectiviruses Sato and Sole with more classical OB-fold SSBs, including the previously mentioned SSBs from S. aureus, B. subtilis and H. pylori and, the second cluster containing other betatectiviruses (i.e., Bam35, GIL01, GIL16 and AP50) along with protein-primed replicating phages belonging to the subfamily Picovirinae (family Salasmaviridae ).…”
Section: Resultsmentioning
confidence: 99%
“…Inverted terminal repeats (ITR) are shown as red arrows at both ends of the genomes. The color key at the bottom-right indicates known and postulated gene functions [ 4 , 10 , 22 , 23 , 44 , 45 , 46 ]. Three genetic modules based of functional grouping, together with the highly variable region (HVR), are indicated above the genomes.…”
Section: Figurementioning
confidence: 99%
“…Contrary to structural viral proteins that are very interconnected through host proteins, those involved in ‘Gene regulation & genome replication’ interact independently. This is the case, for example, of the B35SSB (P2) [52] which remains outside of the network, interacting only with an Acetate coA transferase and a primosomal protein. In general, the obtained network shows a highly interconnected system where some viral proteins could act as hubs in the bacteria-virus interactome [53].…”
Section: Resultsmentioning
confidence: 99%